Comprehensive analysis by liquid chromatography Q‐Orbitrap mass spectrometry: Fast screening of peptides and organic molecules. (18th April 2018) - Sardela, V. F.; Martucci, M. E. P.; de Araújo, A. L. D.; Leal, E. C.; Oliveira, D. S.; Carneiro, G. R. A.; Deventer, K.; Van Eenoo, P.; Pereira, H. M. G.; Aquino Neto, F. R.
Abstract: The number of substances nominally listed in the prohibited list of the World Anti‐Doping Agency increases each year. Moreover, many of these substances do not have a single analytical target and must be monitored through different metabolites, artifacts, degradation products, or biomarkers. A new analytical method was developed and validated for the simultaneous analysis of peptides and organic molecules using a single sample preparation and LC‐Q‐HRMS detection. The simultaneous analysis of 450 target molecules was performed after cleanup on a mixed‐mode solid‐phase extraction cartridge, combined with untreated urine. The cleanup solvent and reconstitution solvent were the most important parameters for achieving a comprehensive sample preparation approach. A fast chromatographic run based on a multistep gradient was optimized under different flows; the detection of all substances without isomeric coelution was achieved in 11 minutes, and the chromatographic resolution was considered a critical parameter, even in high‐resolution mass spectrometry detection. The mass spectrometer was set to operate by switching between positive and negative ionization mode for FULL‐MS, all‐ion fragmentation, and FULL‐MS/MS 2 . The suitable parameters for the curved linear trap (c‐trap) conditions were determined and found to be the most important factors for the development of the method. Only FULL‐MS/MS 2 enables the detection of steroids and peptides at concentrations lower than the minimum required performance levels set by World Anti‐Doping Agency (1 ng mL −1 ). The combination of the maximum injection time of the ions into the c‐trap, multiplexing experiments, and loop count under optimized conditions enabled the method to be applied to over 10 000 samples in only 2 months during the 2016 Rio Summer Olympic and Paralympic Games. The procedure details all aspects, from sample preparation to mass spectrometry detection. FULL‐MS data acquisition is performed in positive and negative ion mode simultaneously and can be applied to untargeted approaches.